Preventing the formation of CaCO3 scales: molecular dynamic simulation study on the role of sodium triphosphate as scale inhibition - Liu, Youquan; Jing, Xianwu; Zhang, Bojian; Jiang, Fan; Pan, Keyu (Journal of the Korean Physical Society, 2024)
To prevent CaCO 3 scaling in oil and gas wells, scale inhibition are commonly used. This study utilized the molecular dynamics method to simulate the crystallization of a high concentration CaCO 3 solution, with particular attention given to the influence of the scale inhibitor sodium tripolyphosphate (Na 5 P 3 O 10 ). Examination of the distribution of CO 3 2− surrounding Ca 2+ indicated that P 3 O 10 5− effectively hinders the interaction between CO 3 2− and Ca 2+ , leading to a decrease in the root mean square displacement and diffusion coefficient of ions. Based on the analysis of intermolecular interaction energies, it is evident that the binding energy between Ca 2+ and CO 3 2− is estimated at around 550 kcal/mol, whereas the binding energy between Ca 2+ and P 3 O 10 5− is approximately 1000 kcal/mol. These data support the conclusion that P 3 O 10 5− exhibits a higher affinity for Ca 2+ binding, thereby impeding the formation of CaCO 3 .